Zinc enriched wheat, maize and rice grain: Specification - Reinberg, Chelsea; Walton, Jenny; Pfeiffer, Wolfgang H.; Boy, Erick; Taleon, Victor; Virk, Parminder (BSI Standards Limited, 2021)
This PAS will focus on crops enriched with zinc through biofortification (breeding or agronomic) technology. Billions of people around the world are at risk of zinc deficiency. Zinc is an essential micronutrient that is important for several functions in the body, including: growth and development; immune system function; reproductive health; and healthy body tissues. When consumed daily, zinc enriched maize, rice and wheat could contribute 35% to 80% of daily zinc needs for women and young children.